Probiotics enhances anti‐tumor immune response induced by gemcitabine plus cisplatin chemotherapy for urothelial cancer. Issue 3 (30th November 2022) - Miyake, Makito; Oda, Yuki; Owari, Takuya; Iida, Kota; Ohnishi, Sayuri; Fujii, Tomomi; Nishimura, Nobutaka; Miyamoto, Tatsuki; Shimizu, Takuto; Ohnishi, Kenta; Hori, Shunta; Morizawa, Yosuke; et al.
Abstract: Chemotherapy drugs, such as gemcitabine and cisplatin (GC), are frequently administered to patients with advanced urothelial carcinoma, however the influence of the gut microbiota on their action is unclear. Thus, we investigated the effects of GC on the gut microbiome and determined whether oral supplementation with a probiotics mixture of Lactobacillus casei Shirota and Bifidobacterium breve enhanced the anti‐tumor immune response. After subcutaneous inoculation with MBT2 murine bladder cancer cells, syngenic C3H mice were randomly allocated into eight groups. The gut microbiome cluster pattern was altered in both the GC and oral probiotics groups ( p  = 0.025). Both tumor‐bearing conditions (no treatment) and GC chemotherapy influenced Pseudoclostridium, Robinsoniella, Merdimonas, and Phocea in the gut. Furthermore, comparison of the GC‐treated and GC + probiotics groups revealed an association of four methyltransferase family enzymes and two short‐change fatty acid‐related enzymes with oral probiotics use. A significant difference in tumor volume was observed between the GC and GC + probiotics groups at week 2 of treatment. Additionally, decreased recruitment of cancer‐associated fibroblasts and regulatory T cells, and activation of CD8 + T cells and dendritic cells were observed in the tumor microenvironment. Our findings reveal the positive effects of a probiotics mixture of Lactobacillus and Bifidobacterium in enhancing anti‐tumor effects through the gut–tumor immune response axis. Future clinical trials are needed to evaluate the full benefits of this novel supplement with oral probiotics in patients with advanced urothelial carcinoma. Abstract : We investigated the effects of gemcitabine plus cisplatin (GC) chemotherapy on the gut microbiome and determined whether oral supplementation with a probiotics mixture of Lactobacillus casei Shirota and Bifidobacterium breve could improve the anti‐tumor response induced by GC chemotherapy. We found altered levels of gut microbiota and increased infiltration of CD8 + T cells and dendritic cells in the tumor microenvironment of GC + probiotics group compared with the GC group. We believe that our study makes a significant contribution to the literature, because our findings highlight the anti‐tumor responses induced by a probiotics mixture of Lactobacillus and Bifidobacterium during GC chemotherapy.